"The World Has to Stop Discriminating Against African American Language" (AAL): Exploring the Language Ideologies of AAL-Speaking Students in College Writing. (April 2023) - Hankerson, Shenika
Drawing on recent decades, literature in college writing that theorizes the importance of Critical Language Awareness (CLA) curricula for African American Language (AAL)-speaking students, this article offers empirical evidence on the design and implementation of a college writing curriculum centered on CLA and its influence on AAL–speaking students' language ideologies with respect to both speech and writing . Qualitative analyses of students' pre- and-post-Questionnaires and the researcher's field notes demonstrate that the curriculum helped students view AAL as an independent, natural, and legitimate language and view themselves as critically conscious thinkers and writers—more likely and willing to develop their academic writing skills and the strategies that support employing their native language in writing—for example, code-meshing strategies. This study offers important implications for college writing instruction.